INVASION OF HOSTILE ALIEN WEED PARTHENIUM HYSTEROPHORUS L. IN WAH CANTT, PAKISTAN - T. Riaz; A. Javaid (Journal of Animal and Plant Sciences, 2009)
A survey of Wah Cantt district Rawalpindi was carried out in April 2007 to study the invasion and distribution of an alien invasive weed parthenium (Parthenium hysterophorus L.). Eight wastelands, each of about 1 ha area were selected in different areas of Wah Cantt. Sampling was done with 1 m2 quadrate. Data regarding prevalence, absolute and relative frequency, and absolute and relative density of parthenium and other weeds of the area were recorded. A total of 44 weed species belonging to 24 families of angiosperms were recorded in the studied area. Parthenium was found in all the eight studied sites showing 100% prevalence. Parthenium was the second most frequently occurring weed in the study area with absolute frequency (AF) of 76% and relative frequency (RF) of 3.92%, after Cannabis sativa with 86% AF and 4.28% RF, respectively. Similarly C. sativa and parthenium were found the two most densely populated weeds with 1.82 and 1.63 absolute density (number of plants m-2) and 6.68 and 5.99% relative density, respectively. The present study revealed that the parthenium has attained the second most frequently and densely occurring weed in the area. There is fear that because of its high reproductive potential, fast growth rate, allelopathic nature and high adaptability to the prevailing environmental conditions, it may attain the status of dominating weed in the studied and surrounding areas. Therefore, there is need for an urgent parthenium management strategy to stop further spread of this noxious alien weed in the area.
Keywords: Absolute density; Alien weed; Parthenium hysterophorus; Relative density